Modifikasi Altmant Z Score dan Integrasi Nilai Islam sebagai Factor Pengaruh Financial Distress terhadap RGEC (Studi Kasus BNI Syariah, BRI Syariah, Bank Syariah Mandiri) - Sahrani; Mutmainah juniawati (Universitas Muhammadiyah Prof Dr Hamka, 2020)
The survival of a company/ institution depends on several things. When a company / institution starts showing poor health, a financial manager must immediately take action so that the company / institution approaches safe conditions, one of the methods used is through financial distress identification. Identification of financial distress conditions is more important than bankruptcy, because companies / institutions will definitely experience financial distress first and then go bankrupt. Islamization of Knowledge is not a new thing in the development of Islamic economics. The integration of Islamic values ​​into existing theories is a mandate for the entire academic community. This research aims to make an integration of knowledge in the field of Islamic economics in describing and analyzing the effect of RGEC (Risk Profile, GCG, Earnings, and Capital) on Financial Distress after adding Islamic values ​​to BRI Syariah, BNI Syariah and Bank Syariah Mandiri in 2012- 2018. This study shows that the variables X1 (NPF), X2 (FDR), X3 (GCG), X4 (ROA), X5 (CAR) simultaneously influence the Islamic Financial Distress where the model used is PLS (Pooled Least Square). The analytical method used is panel data regression through the calculation of the Z Z Score where the data processing method uses Panel Data regression which is processed using STATA and SPSS. Keywords: Financial Distress, Islamic Financial Distress, RGEC, Altman Z Score, Regression Panel Data, STATA, SPS.